Wild Lonicera caerulea berry polyphenol extract reduces cholesterol accumulation and enhances antioxidant capacity in vitro and in vivo. (May 2018) - Liu, Suwen; You, Lu; Zhao, Yuhua; Chang, Xuedong
Abstract: The hypocholesterolemic effect of Lonicera caerulea berry extract rich in polyphenols (LCBP) on high cholesterol-induced hypercholesterolemia and lipoprotein metabolite changes was examined in Caco-2 cells and rats. Cyanidin-3-glucoside, catechin, and chlorogenic acid are the major phenolic components of LCBP. The cholesterol-reducing effect and antioxidant capacity of these components were compared in Caco-2 cells. LCBP (80 μg/mL) and cyanidin-3-glucoside, catechin, and chlorogenic acid (50 μM) were found to be effective (p < 0.05). Rats were fed a high cholesterol diet (HCD) with or without LCBP supplementation (75, 150, and 300 mg/kg body weight intragastrically once daily) for 12 weeks. Compared with the HCD control group, LCBP supplementation at 150 and 300 mg/kg decreased the levels of TC, TG, and LDL-C, but increased that of HDL-C. LCBP treatment promoted greater neutral and acidic sterol excretion (p < 0.05) and improved the antioxidant capacity of the colon tissue, colon contents, and blood. Moreover, trimethylamine N-oxide (TMAO) levels were decreased in serum (p < 0.05). NPC1L1, ACAT2, and MTP mRNA and protein expression were reduced and ABCG5/8 expression was increased (p < 0.05) after LCBP treatment. Our results suggest that LCBP could be used as a functional food for the prevention and treatment of diseases related to excessive cholesterol accumulation. Graphical abstract: LCBP inhibited cholesterol absorption via down-regulated cholesterol absorption gene mRNA and protein expression and increased antioxidant capacity in vitro and vivo. Highlights: The cholesterol-lowering activity of LCBP was investigated in rats by HCD. LCBP normalized abnormal serum TC, TG, HDL-C, and LDL-C levels. The cholesterol-reducing effect of C-3-G, catechin, and CA were compared in cells. LCBP downregulates cholesterol absorption gene. LCBP improved colon and serum antioxidant capacity.